Region-integrating or region-disintegrating? The social groups of medieval Silesia examined in the context of their political activity (from the last decades of the 12th century to the 15th century) - Wiszewski, Przemysław (Publishing House eBooki.com.pl, 2013)
Activities of social groups, which develop relations between the members of a society, constitute a crucial aspect of every region’s character. Did the political and social elite of the Odra region in the period from the latter part of the 12th century to the latter part of the 15th century engage in intentional and coordinated activity? Or did they, after being forced by external factors to take such action, continue to coordinate their activities after these external factors ceased to be operative? Yet another question is whether the members of this political elite considered the notion of a unified, territorial unit called “Silesia” in their activities? Various political undertakings of the Odra region’s elite in the Middle Ages makes establishing a unified model of the formation of regional unity unfeasible. Joint political actions undertaken by the dukes maintained an awareness of Silesia’s unity despite their and their courts’ tendency to focus on the importance of their particular duchies. The dukes, via conventions and confederations, focused their activities on building a sense of regional community. Despite extensive cooperation on various issues which crossed the borders of individual duchies, separatist tendencies were still visible in the latter part of the 14th and early 15th centuries. Silesian society, forged through the political activities of its elite, was by nature a network which reacted dynamically to influences from its external environment. At times the structure may have hardened, although its members valued their local identity at least as greatly as their regional one.
Keywords: Silesia; social history; regional history; regiogenesis